PENGARUH FAMILY SUPPORT GROUP TERHADAP KEPATUHAN DIET PASIEN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS KOTA TANGERANG - Musripah, Nana Supriyatna, Sigit Mulyono (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK)
Diabetes Mellitus is a disease that cannot be cured and if it is not handled properly, it can lead to various complications such as stroke, coronary heart disease, kidney failure, blindness, diabetes wounds and organ amputation. The family support group intervention aims so that diabetes mellitus patients can feel the support and attention of their families so that they can lead a quality life even with diabetes mellitus, and there are no complications. This study aims to analyze the effect of family support groups on dietary compliance in patients with diabetes mellitus. The research design used a quasi? experimental approach with pre and post control group with a sample size (n) = 64 which was divided into two groups, namely intervention and control with 32 respondents each. Data analysis using the Wilcoxon test showed significant differences in family support group dietary adherence in Diabetes Mellitus patients before and after joining the Family Support Group with p value = 0.000 (p <0.05) and there was no significant difference in dietary adherence in Diabetes Mellitus patients before and after without being given a family support group with p = 0.616 (p> 0.05). The results of this study are expected to make family support groups as one of the nursing interventions to improve dietary compliance in diabetes mellitus patients. Keywords: diabetes mellitus, diet compliance, family support group